2001
DOI: 10.1097/00001721-200107000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic therapy with enoxaparin during l-asparaginase treatment in children with acute lymphoblastic leukemia

Abstract: Forty-one consecutive children with acute lymphoblastic leukemia (ALL) received prophylaxis therapy with the low molecular weight heparin (LMWH) enoxaparin during L-asparaginase treatment. Enoxaparin was given every 24 h subcutaneously at a median dose of 0.84 mg/kg per day (range, 0.45-1.33 mg/kg per day) starting at the first dose of L-asparaginase until 1 week after the last dose. Molecular analysis for thrombophilic polymorphisms documented prothrombin G20210A mutation in 3/27 (11%), homozygosity for MTHFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 12 publications
2
109
1
3
Order By: Relevance
“…However, the safety of those agents in such patients is unknown, and there are potential issues with the newer agents concerning drug interactions and difficulties in reversing bleeding. Antithrombin iii concentrates have been used effectively in the induction setting 15 ; however, its routine use in a prolonged intensification phase would be impractical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the safety of those agents in such patients is unknown, and there are potential issues with the newer agents concerning drug interactions and difficulties in reversing bleeding. Antithrombin iii concentrates have been used effectively in the induction setting 15 ; however, its routine use in a prolonged intensification phase would be impractical.…”
Section: Discussionmentioning
confidence: 99%
“…Few data have been reported about the prevention of vte in such patients. A study in pediatric all patients treated with an asparaginase-containing regimen demonstrated that the use of low-molecular weight heparin (lmwh) prophylaxis was associated with a low risk of vte 15 ; however, the control group in that study had only a 4% vte rate. A prospective nonrandomized study in children with all, comparing antithrombin alone with antithrombin plus lmwh, found that prophylaxis with enoxaparin was associated with a lower proportion of vte (12.7% vs. 0%, p = 0.02), without an increase in bleeding complications 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Although this study demonstrated no clear evidence of the reduced levels of these proteins in identifying at-risk patients, this may have been related to small sample size. An Israeli pediatric study (n = 41) utilizing enoxaparin prophylaxis (discussed later in detail) demonstrated a high incidence of genetic thrombophilia in 27 children (11% prothrombin G20210A and 18% factor V Leiden), who were Arabs and Jews in ethnic origin; however, no one had any VTE [31].…”
Section: Identification Of High-risk Patientsmentioning
confidence: 99%
“…A nonrandomised study of 41 paediatric patients with ALL using the low molecular weight heparin (LMWH) enoxaparin as prophylaxis during L-Asp therapy reported no thrombotic events during 76 courses of L-Asp, with 1 brain infarct reported 7 days after cessation of prophylaxis. 66 LMWH has also been used successfully as secondary prophylaxis in patients re-exposed to L-Asp following an initial VTE without recurrence or excess bleeding. 67 However, there remains concern that heparins, which rely on AT for their mechanism of action, may not be the most appropriate option.…”
Section: Thromboprophylaxismentioning
confidence: 99%